Análise dos syllabi de Português Língua Estrangeira em universidades estadunidenses - Ferreira, Wanessa Monte (2020)
The syllabus is almost ubiquitous in the academic life. Syllabi provide the content to be taught, the work methodology of the professor, and the assessments to be undertaken by the students, based on the characteristics of the course, the degree and the class group. As the syllabi provide the standards for how classes should be conducted, they provide us with a partial knowledge how the content must be taught in the classroom. This master thesis works along the lines of the Applied Linguistics, specifically for the teaching and learning of languages. It analyzes the syllabi of six courses of Portuguese as a Foreign Language (PLE) out of five different universities in the USA. Our main purpose, the understanding of such dynamics in those syllabi, was achieved following some specific purposes along the way, such as the analysis of how the syllabus genre is created and its contribution to the social action and event interaction, the identification of syllabi types and the methodologies used, and the analysis of how the proposed purposes relate to the assessments, which makes this work into a qualitative, documentary and bibliographical research (Gil 2002). The methodological take in our research was based on the language acquisition theories (Krashen 1984, Swain 1985, 2005) and the communicative approaches found in language teaching in the USA (Richards 2006). As for the types of syllabi studied herein, we followed the studies of Rahimpour (2010), Nunan (2001) and Krahnke (1987). Concerning the definitions of syllabi and their use by professors and students, we based these on Altman (1992), Gannon (2018) and O’Brien, Mills, and Cohen (2008). Finally, the analysis of the syllabus genre was undertaken having in mind the generic structure and the purposes (Fairclough 2003) for said genre. Data interpretation shows us that although the analyzed syllabi come from different moments of preparation and universities, they share the same explicit purposes. At the same time, we have found that the Purposes and the Description of the course do not always correspond to what is effectively taught.